Study of a thermoelectric generator based on a catalytic premixed meso-scale combustor. (15th January 2016) - Merotto, L.; Fanciulli, C.; Dondè, R.; De Iuliis, S.
Highlights: A catalytic meso-scale combustor fueled with propane/air is developed and tested. The combustor is coupled with thermoelectric modules for electric power production. The system produces 9.86 W electrical power with an overall efficiency up to 2.85%. Abstract: The recent advances in miniaturized mechanical devices open exciting new opportunities for combustion, especially in the field of micro power generation, allowing the development of power-supply devices with high specific energy. The development of a device based on a catalytic combustor coupled with thermoelectric modules is particularly appealing for combustion stability and safety. Furthermore, when implemented in micro/meso scale devices, catalytic combustion allows full utilization of hydrocarbon fuel's high energy densities, but at notably lower operating temperatures than those typical of traditional combustion. These conditions are more suitable for coupling with conventional thermoelectric modules since they prevent the modules' degradation. In this work a novel catalytic meso-scale combustor fueled with propane/air mixture has been coupled with two conventional thermoelectric modules. The wafer-like combustor is filled with commercially available catalytic pellets of alumina with Platinum (1% weight). Temperature measurements, in terms of point values and 2D distribution across the combustor surfaces, were carried out in different operating conditions. Exhaust gases concentration measurements and pellet aging investigation were performed to determine the combustor efficiency and stability. Starting from these results the combustor has been coupled to bismuth telluride-based thermoelectric modules using a water cooled heat exchanger at the cold side. The system obtained produces 9.86 W of electrical power reaching an overall efficiency up to 2.85%: these results represent an improvement in portable-scale electrical power production from hydrocarbon fuels state-of-art. Moreover, the voltage and current characteristics allow using such generator for small portable devices power supplying.